(untitled) (Architecture Image Studies, 2025)
The urbanized built environment is expanding rapidly in developing nations, and there is an urgent need to implement green building principles to make design and construction methods there more sustainable. Cities have seen an increase in built-up areas, and new construction projects that use the green building idea can undoubtedly lessen the environmental impact of buildings. However, the region surrounding urban settlements was likely occupied prior to the second millennium BC, and there is proof that people have lived there continuously from at least the sixth century B.C. Therefore, in addition to new construction, there is a significant chance that existing structures could have a negative environmental impact if their maintenance and operation practices are not examined. Government regulations pertaining to energy and water use as well as CO2 emissions will need to include mandatory limitations. The performance of existing buildings can be enhanced by a number of important sustainability improvements, in addition to energy and water efficiency, such as structural evaluation, resource use, disaster resilience, waste reduction through recycling programs, sustainable procurement and purchasing practices, and continuing operations and maintenance practices. Employee comfort and indoor environmental quality are two "intangible" benefits of green buildings that are difficult to measure but just as crucial to consider as the tangible ones. "Indoor Environmental Quality (IEQ)" includes things like views, air quality, natural lighting, thermal and physical comfort, and the ability to manage one’s surroundings, all of which have beneficial psychological and physical benefits and help make residents happier and healthier.